2010
DOI: 10.1111/j.1475-6811.2010.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parental divorce on young adults' romantic relationship dissolution: What makes a difference?

Abstract: It was proposed that parental divorce does not have a uniform effect on young adults' romantic relationships and that differential outcomes depend on how young adults perceive their parents' divorce. Using a sample of 571 young adults, structural equation modeling suggested that, compared with those from intact families, young adults whose parents divorced held a more favorable attitude toward divorce. A positive attitude toward divorce was associated with lower commitment to their romantic relationship, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 64 publications
3
45
0
3
Order By: Relevance
“…Some studies have found that in premarital or dating relationships, young adults whose parents had divorced were associated with lower relationship satisfaction, more conflict, and less commitment (Cui & Fincham, 2010;Rhoades, Stanley, Markman, & Ragan, 2012;Whitton et al, 2008). Research has also suggested that divorce or conflictual parental relationships have a negative impact on the attitudes of young adults about marriage and commitment (Cui, Fincham, & Durtschi, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have found that in premarital or dating relationships, young adults whose parents had divorced were associated with lower relationship satisfaction, more conflict, and less commitment (Cui & Fincham, 2010;Rhoades, Stanley, Markman, & Ragan, 2012;Whitton et al, 2008). Research has also suggested that divorce or conflictual parental relationships have a negative impact on the attitudes of young adults about marriage and commitment (Cui, Fincham, & Durtschi, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Existing evident indicated that individuals who experienced parental divorce are at greater risk to divorce themselves in later years (Cui, Fincham, & Durtschi, 2011;Teachman, 2002), signalling a need of research focusing on offspring of divorced families.…”
Section: Attitudes Towards Marriage Following Parental Divorcementioning
confidence: 99%
“…One possible mechanism which might greatly affect adolescents is the exposure to inter-parental conflict. Research consistently displayed that adolescents who are exposed to intense inter-parental conflict have greater tendency to perceive negative attitudes towards marriage (Cui et al, 2011;Jennings, Salts, & Smith, 1992;Tasker, 1993;Tasker & Richards, 1994;Valerian, 2001). For example, Dennison and Koerner (2006) found a significant negative relationship between inter-parental conflict and attitudes towards marriage among adolescents who aged from 11 to 17 years old.…”
Section: Mechanism Affecting Attitudes Towards Marriage Among Adolescmentioning
confidence: 99%
“…(Lucila,47) Based on the experiences of their divorces, separations, teenage pregnancy (in the case of Eli, 26), domestic violence, and irresponsible partners, one of the participants' greatest fears is that these patterns continue in the lives of their sons and daughters. In their study dealing with the impact of divorce on children, Cui, Fincham, and Durtschi (2010) show that although there exists a high likelihood of divorce in the lives of the children of divorced parents, it is not a total given and their ultimate decision to dissolve their marriage would depend on numerous factors. The mothers, in this study, are more determined to invest time and dedication to their own sons and daughters.…”
Section: Their Experiences As Single Parentsmentioning
confidence: 99%